Solving a Problem of Adaptive Stabilization for Some Static MIMO Systems - Zhiteckii, L.S.; Azarskov, V.N.; Solovchuk, K.Yu. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to show that it is possible to stabilize any uncertain multivariable static plant which gain matrix may be either square or nonsquare and may have an arbitrary rank remaining unknown for the designer. Methods. The methods based on recursive point estimation of unknown plant parameters are utilized to design the adaptive inverse model-based controller. Results. The asymptotic properties of the adaptive controllers have been established. Simulation results have been presented to support the theoretic studies.